A escuta psicanalítica de aspectos da vida subjetiva na Defensoria Pública do Estado de Mato Grosso - Bittencourt, Daniely Cristina Souza (2022)
The dissertation consists of the presentation of scenes that were constructed by the researcher, based on field diaries, arising from her daily experiences at the Public Defender's Office of the State of Mato Grosso, in 2018, whose internship practice was linked to the last year of degree in Psychology and the Project Weekly Meetings for Research and Clinical Studies . For this, there is a bet on the experiences that were produced in this institutional routine; This is where the creative power of this work comes from. Thus, the objective is to bring fragments of scenes experienced in the DPEMT: “Ana teaches us”; “Pieces of Marias in many of us (women in Brazil)” and “What do I do with what happens to me? Alice in (us) – humans – were conceived having psychoanalysis as an epistemological-methodological scope. With this in mind, the notion of event is worked as something of its own, coined in the object of psychoanalysis, that is, to what is immaterial, unobservable, unknowable, but which produces estrangement effects. In this way, the event brought about in the order of the unknowable is questioned: would it be linked to the order of the pre-linguistic, the pre-representational? Is it corporeal and instinctual? By the researcher of this work the event is felt as restlessness, restlessness and can only gain representational contours through language: transference over the word. The language apparatus allows transferring onto words what, the first, was felt as restlessness, as malaise. In methodological terms, the data construction procedure consisted of transcribing the content recorded on paper, to the computer, of all field diaries, produced in the internship held at the Public Defender's Office of the State of Mato Grosso, in 2018. In this transition, they respected All the information present in the physical and original documents must be used. Subsequently, the material was read and the scenes to be worked on in the dissertation were chosen. The propensity for this plot came from the researcher's interest in focusing on the stories of Ana, Maria and Alice – characters who composed the experiences during the internship. The construction was designed together with the Only After Research group – dedicated to discussions and research constructions that use psychoanalysis as a theoretical framework. In this approach, the group works under the condition of a brake on the thrust of understanding. In this way, it was possible to design the research results, intertwining the researcher's experiences and experiences – as a singular person/subject (of the unconscious) – with her presence in the research as a psychologist with a psychoanalytic orientation; the remains of meanings made possible through the transfer with the work field in the Public Defender's OfficeMT; and the materials produced, also, through transfer (research work on the effects of the institution's events - on me); and, finally, what was possible from this experience to make material shareable, through writing.